Thermal and energy evaluation of a novel polymer-ceramic composite as insulation for a household refrigerator (2015)
This article presents a feasibility study of a new polymer-ceramic composite material applied as a thermal insulator on the surface of a low net volume household refrigerator. This paper describes its manufacture in a succinct manner, and a thermal and energy comparison between the factory refrigerator and the refrigerator with the composite installed. Based on the experiments, it is concluded that when using the composite, the average internal temperature of the fridge is increased by 1°C, for practical and design purposes, the refrigerator still functions below 3°C. It was also found that at stable operating conditions the energy consumption using the composite saves approximately 1.5%. Despite these slight savings, the pyro-expanded perlite composite acts as a thermal isolating material. This material may exhibit better ease of use and thermal, energetic and economic benefits, without omitting the environmental characteristics that they favor.